Salvianolic acid B: a promising cardioprotective agent - Shao, Yingchun; Zhai, Li; Jiang, Shan; Sun, Fusheng; Liu, Xuedong (Frontiers in Immunology, 2025)
Salvia miltiorrhiza Bunge [Lamiaceae; Salviae miltiorrhizae radix et rhizoma] is a core herb in traditional Chinese medicine widely used for treating cardiovascular diseases (CVD). Its key bioactive compound, salvianolic acid B (SalB), has emerged as a promising therapeutic agent for CVD. Modern pharmacological studies have demonstrated that SalB exerts comprehensive cardioprotective effects through multiple mechanisms, including antioxidant and anti-inflammatory activities, induction of mitochondrial autophagy, enhancement of endothelial function, anti-fibrotic actions, and improvement of hemorheology. These properties underscore its significant value in both the prevention and treatment of CVD. However, current research on SalB in the context of CVD remains relatively fragmented. To address this gap, this review systematically consolidates existing research findings on SalB in the cardiovascular field, providing an in-depth analysis of its sources, pharmacological mechanisms, efficacy characteristics, compatibility strategies, and dosage form optimization. Furthermore, by integrating both preclinical and clinical data, this review comprehensively evaluates the safety and efficacy of SalB, aiming to offer theoretical support and clear research directions to facilitate the substantive transformation of this traditional bioactive compound into a modern CVD therapeutic drug.